Satisfacción del cliente de la Empresa C-Smart de la ciudad de Babahoyo, periodo 2022. - Mendoza Cruz, Lilibeth Tatiana (2023)
The company C-Smart Babahoyo, is a private entity and began its operations in the City of Babahoyo in May 2022. This company is specifically dedicated to the commercialization of technology equipment such as sales of cell phones, laptops, computers, and accessories. . The company is located on 5 de Junio street between Pedro Carbo street and 27 de Mayo street. It has its headquarters in the city of Guayaquil and maintains branches in various cities. The objective of the investigation consisted of knowing the level of satisfaction that the clients of the company C-Smart of the city of Babahoyo have. In the present investigation it was considered pertinent to use the line of investigation: Administrative, Tax, Financial Management, Audit and Control, as well as the sub-line of investigation: Marketing and Commercialization, which are raised by the Commerce Career. A descriptive methodology was used with qualitative and quantitative characteristics, being able to obtain relevant information through the interview and survey technique. Among the main results found, it is found that, although the C-Smart company is very young in the market, it has a good acceptance, due to customer service, quality of its products and information given to customers, facilities payment for customers, fulfillment of expectations of its users.